Three-Dimensional Growth of Prostate Cancer Cells Exposed to Simulated Microgravity - Dietrichs, Dorothea; Grimm, Daniela; Sahana, Jayashree; Melnik, Daniela; Corydon, Thomas J.; Wehland, Markus; Krüger, Marcus; Vermeesen, Randy; Baselet, Bjorn; Baatout, Sarah; Hybel, Trine Engelbrecht; Kahlert, Stefan; et al. (Frontiers in Cell and Developmental Biology, 2022)
Prostate cancer metastasis has an enormous impact on the mortality of cancer patients. Factors involved in cancer progression and metastasis are known to be key players in microgravity (µg)-driven three-dimensional (3D) cancer spheroid formation. We investigated PC-3 prostate cancer cells for 30min, 2h, 4h and 24h on the random positioning machine (RPM), a device simulating µg on Earth. After a 24h RPM-exposure, the cells could be divided into two groups: one grew as 3D multicellular spheroids (MCS), the other one as adherent monolayer (AD). No signs of apoptosis were visible. Among others, we focused on cytokines involved in the events of metastasis and MCS formation. After 24h of exposure, in the MCS group we measured an increase in ACTB, MSN, COL1A1, LAMA3, FN1, TIMP1, FLT1, EGFR1, IL1A, IL6, and CXCL8 mRNA expression, and in the AD group a raise in LAMA3, COL1A1, FN1, MMP9, VEGFA, IL6, and CXCL8 mRNAs compared to samples subjected to 1g conditions. Significant downregulations in AD cells were detected in the mRNA levels of TUBB, KRT8, IL1B, IL7, PIK3CB, AKT1 and MTOR after 24h. The release of collagen-11 and fibronectin protein in the supernatant was decreased, whereas the secretion of IL-6 was elevated in 24h RPM samples. The secretion of IL-1α, IL-1β, IL-7, IL-2, IL-8, IL-17, TNF-, laminin, MMP-2, TIMP-1, osteopontin and EGF was not significantly altered after 24h compared to 1g conditions. The release of soluble factors was significantly reduced after 2h (IL-1α, IL-2, IL-7, IL-8, IL-17, TNF-, collagen-11, MMP-2, osteopontin) and elevated after 4h (IL-1β, IL-2, IL-6, IL-7, IL-8, TNF-, laminin) in RPM samples. Taken together, simulated µg induced 3D growth of PC-3 cancer cells combined with a differential expression of the cytokines IL-1α, IL-1β, IL-6 and IL-8, supporting their involvement in growth and progression of prostate cancer cells.